PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR SISTEM PERSAMAAN LINEAR DUA VARIABEL - Alfina Dwi Puspita; Anetha L.F. Tilaar; Santje M. Salajang (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Alfina Dwi Puspita. 19504056. The Influence of the Student Team Achievement Division Type Cooperative Learning Model on Learning Results of Two-Variable Linear Equation Systems. Thesis. Mathematics Department. Faculty of Mathematics, Natural and Earth Sciences. Manado State University. Tondano. 2023. This research aims to examine student learning outcomes in the Student Team Achievement Division type learning model and conventional learning models at SMP Negeri 1 Airmadidi.  This research method is Quasi Experiment research and the research design uses a Non-Equivalent Control Group Design. Data collection using pretest and posttest. This research was attended by 25 students from class VIIIG as the control class and VIIIH as the experimental class. Sampling was taken by random sampling. The data analysis techniques used are prerequisite testing and hypothesis testing. The results of the research show that there are differences in learning outcomes using the Student Team Achievement Division learning model which are higher than conventional learning models